Pathways to the US Supreme Court from the arena to the monastery - Nelson, Garrison; Steakley, Maggie; Montague, James; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Pathways to the U.S. Supreme Court is a quantitative-historical recapitulation of the routes taken to the US Supreme Court by the 112 Justices who were confirmed by the Senate and served, and the 28 others whose candidacies for confirmation were defeated, withdrawn, or declined.
Keywords: Science; Science; Science, general